(3JMQjQ cJGH eGfGdGhS aj CTcGdG GdcQIs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3eGfGdGhSs
(3ChdgG (B:s
(3Efi cfJ CQjO Cf CMQQ GdcJH GdehSheI HGdJehjVGJ CYfi GdcJH GdJi ef TCfgG Cf JJhSW ai GdJQJjH s
(3BNQgG (B:s
(3Je GdcJGH hGdMeO ddg s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B31 s
(3eUOQ GbJfGA GdCUd (B:s
(3Sdje GZG (B(743) s
Keywords: (3GdQjGVjGJs